Market exposure, civic values, and rules - Devesh Rustagi (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2023)
Does market exposure shape civic values and rules that constrain opportunistic behavior and foster generalized cooperation? I investigate this question using a natural experiment on market location from Ethiopia, where exchange is prone to cooperation problems from asymmetric information and absence of third-party enforcement. I find a strong negative effect of market distance on civic values and rule formation. These results arise because groups develop different kinds of exchange structures to alleviate cooperation problems from market failure. In groups further away from markets, individuals rely on eponymous exchange and reputation in dense social network, which fosters parochial cooperation. In contrast, in groups near markets, impersonal and ephemeral exchange with strangers creates a demand for civic values and rules, which together with community sanctioning fosters generalized cooperation. Distance from markets without asymmetric information has no effect on civic values and rules.
Keywords: C93; D8; N97; Z13; 330; Markets; civic values; rules; cooperation; market failure; asymmetric information; Ethiopia